Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Disiplin Pegawai : The Influence of Work Motivation and the Work Environment on Employee Discipline - Pipit Shofiatul Hayat Rachman; Ulta Rastryana (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Employee discipline serves as an indicator of adherence to the regulations implemented within acompany. This aspect encompasses compliance with working hours, punctuality in task completion, and adherence to procedures and policies that support organizational effectiveness and productivity. This study aims to analyze the influence of work motivation and work environment on employee discipline at the Regional Disaster Management Agency (Badan Penanggulangan Bencana Daerah) Office of Tangerang Regency. The population in this study includes all employees of the office, with a sample size determined using the Slovin formula, resulting in a total of 133 respondents. This research employs a quantitative approach, with data collected through questionnaires. Data analysis was conducted using IBM SPSS software version 26. The analytical techniques applied include descriptive analysis, validity and reliability testing, classical assumption tests (normality test, heteroscedasticity test, and multicollinearity test), multiple linear regression analysis, and hypothesis testing (ttest, F-test, and coefficient of determination test). The findings indicate that work motivation positively influencesemployee discipline, with a significance value of 0.000 < 0.05. Similarly, the work environment has a positive impact on employee discipline, with a significance value of 0.006 < 0.05. The adjusted R Square value obtained is 82.6%, indicating that the influence of work motivation and work environment on employee discipline falls within the low category.